The Roles of Notary in Living Environment Conservation - Luh Putu Sudini (NOTARIIL Jurnal Kenotariatan, 2020)
Humans as one of the objects of life face increasingly complex problems leading to a prosperous life. Humans in life towards prosperity in society need a Notary in making a deed. Notary is a legal profession, so the Notary profession is a noble profession (Nobile officium), considering that the notary profession is very closely related to humanity. This study aims to know and understand the role of the notary in Living Environment conservation. This study uses normative legal research methods, with sources of legal materials such as primary legal materials, secondary legal materials and tertiary legal material. Notary is a public official who is authorized to make an authentic deed and has other authority as referred to in this Law or based on other laws. While the Living Environment is a number of objects and conditions that exist in the space we occupy that affect our lives. This Living Environment includes dynamic (biotic) and static (abiotic). The role of a notary in Living Environment conservation is very important, remembering the duties and functions of a notary in the community primarily on making a deed, and a notary in carrying out his profession must pay attention to Living Environment conservation (especially the Living Environment on land) considering the notarial deed has implications on the Living Environment such as land deeds, and so on, which are beneficial to the community.